2017
DOI: 10.3906/sag-1511-101
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical fitness and falling risk and fear of falling in community-dwelling elderly people with different physical activity levels

Abstract: Background/aim: The aim of this research was to determine the effects of physical activity level (PAL) and physical fitness on falling parameters in community-dwelling elderly people.Materials and methods: Seventy-six elderly people were grouped as low PAL group (group 1, n: 38) and high PAL (group 2, n: 38) according to their PAL scores. PAL was measured by the Physical Activity Scale for the Elderly and muscle strength, muscle endurance, aerobic endurance, and flexibility tests were applied; body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
12
0
4
Order By: Relevance
“…Overall, this sample is composed of women who present better results than the cutoff values suggested in literature (e.g., Shumway-Cook, Brauer, & Woollacott, 2000;Tinetti, Richman, & Powell, 1990). It was recently reported that physical activity levels do have a positive effect on falls or risk of falls in elderly people (Duray & Genç, 2017). So it might be considered that the amount of physical activity plays a major role in falls in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this sample is composed of women who present better results than the cutoff values suggested in literature (e.g., Shumway-Cook, Brauer, & Woollacott, 2000;Tinetti, Richman, & Powell, 1990). It was recently reported that physical activity levels do have a positive effect on falls or risk of falls in elderly people (Duray & Genç, 2017). So it might be considered that the amount of physical activity plays a major role in falls in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, dynamic balance, measured by the "Time-Up-&-Go" functional test, and BMD presented a nonsignificant correlation with the FES (Table 1). The literature reported that dynamic balance had a positive relationship with fear of falling (e.g., Bergland & Wyller, 2004;Duray & Genç, 2017). Furthermore, BMD presented a significant relationship with level of physical activity and hence a lower risk of falling (Amiri, Hosseini, Rahmaninia, Nooreddini, & Bijani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, implementing regular monitoring and predicting trends of aging in older adults has been suggested [ 18 20 ]. Recent research also showed that functional fitness tests could reflect different physical activity levels and demonstrate that seniors with high physical activity levels have better fitness performance [ 21 ]. Another previous study suggested that resistance exercises and balance training may have a crossover effect on the functional fitness of the elderly; however, cardiorespiratory fitness and flexibility may require specific interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrates the difference in physical fitness between people with SMI who practise physical activity and those who do not practise physical activity, showing better performance of physical fitness in physically active people. Different physical activity interventions were carried out in which there was shown an improved physical fitness in people with SMI [ 11 , 47 ], however, these interventions should not just focus on aerobic activity but also on increasing the muscle strength and balance of people with SMI and also encourage these people to perform physical activity independently and to decrease the risk of falls similar to those carried out in other populations as elderly people [ 48 ].…”
Section: Discussionmentioning
confidence: 99%